The role of literacy education in preventing the impact of fake news on government policies and socio-political Stability - Ali, Muhammad; Harun, Muhammad Yahya; Kasim, Fajri M; Mursalin, M (Universitas Malikussaleh, 2021)
The aimed of this study is to explore how fake news through the media can disrupt socio-political stability and impede the implementation of various government policies that are being introduced, and how significant efforts are being made by all parties to ensure that hoax coverage does not spread through all lines of social life by providing a literacy education formula in the context of knowledge challenges that are difficult to address. It also analyzes how social media are used to construct strategies that can cloud the atmosphere of socio-political life and public morality, which seem to give priority to pro-people ethics, as is the case in Indonesia. In this study, a qualitative approach and post-truth theory are used as analytical perspectives in the interpretation of topics such as Covid-19 news and details in the presidential election contest of 2019. This study will also document how, through the mediation of hoax reporting through social media, online social media representations such as Facebook, Instagram, WhatsApp, and other personal messaging applications are explored. So, of course, based on the findings of the preliminary observations, there needs to be a strategy for creating new, shifting narratives about different government policies based on relevant references, since modern media have an influence on the social, cultural, and political landscape of life. A proper media literacy and literacy analysis must also be carried out to see if offline communities with limited internet connectivity no longer accept the notion of 'hoax opinion' established in Indonesia. Therefore, literacy education would be able to reveal false knowledge that has spread through society and will correct any myths in social life.